Personalized therapies in advanced BRAFV600-mutated melanoma: review based on 3 case reports of the REMINISCENCE project - Gebhardt, Christoffer; Debus, Dirk; Rohrer, Peter; Kähler, Katharina C.; Koch, Lukas; Terheyden, Patrick; Nguyen, Van Anh (Melanoma management, 2025)
The management of advanced, unresectable, or metastatic BRAFV600-mutated melanoma is complex, particularly regarding therapy sequencing with targeted therapies (TT) and immune checkpoint inhibitors (ICI). The REMINISCENCE project aimed to enhance individualized therapy approaches by analyzing case reports of patients undergoing encorafenib and binimetinib (EB) therapy. This report discusses three melanoma patients with brain metastases treated in Germany and Austria, emphasizing personalized treatment strategies in BRAFV600-mutated melanoma, particularly when both ICI and TT are available. The timing for transitioning between therapies remains contentious, with many patients experiencing disease progression during or after adjuvant therapy. Findings from clinical trials like DREAMseq, SECOMBIT, EBIN, and ImmunoCobiVem may not directly apply to this evolving clinical landscape due to the impact of prior therapies on the tumor microenvironment. The variations in trial designs further complicate sequencing strategies. Emerging methods, such as early circulating tumor DNA (ctDNA)-guided approaches, present potential pathways for personalized treatment. Ongoing research into sequencing therapy is crucial for improving clinical outcomes. To determine the most effective treatment sequences based on individual medical histories, genetic profiles, and treatment goals, there is an urgent need for prospective biomarker-driven clinical trials.